Coders : the making of a new tribe and the remaking of the world - Thompson, Clive, 1968- (Penguin Press, 2019)
"From acclaimed tech writer Clive Thompson, a brilliant and immersive anthropological reckoning with the most powerful tribe in the world today, computer programmers - where they come from, how they think, what makes for greatness in their world, and what should give us pause"--